(untitled) - Noe, Raymond A. (New York, 2007)
Fundamentals of Human Resource Management, by Noe, Hollenbeck, Gerhart and Wright is specifically written to provide a complete introduction to human resource management. While it doesnt cover the depths of human resource management theory, the book is rich with examples and engages students through application. Fundamentals differs from the hardback textbook by the same author team. Instead of a higher level of theory thats geared towards the HRM majors, this book focuses on the uses of human resources for the general business manager. Issues such as strategy are reduced to give a greater focus on how human resources management is used in the everyday work environment. It provides students with the background necessary to manage human resources effectively and to be able to distinguish good from poor human resource management practices and how they impact business.
Keywords: Personnel management,Quản lý nhân sự